2017
DOI: 10.1016/j.crci.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and selective oxidation of aldehydes with dioxygen catalysed by vanadium-containing heteropolyanions

Abstract: The heteropolyacids "H 3þn [PMo 12en V n O 40 ]$aq" (denoted as HPA-n; n ¼ 2, 3, 8) catalyse the oxidation of aldehydes to carboxylic acids in the presence of dioxygen with very good yields. The effect on the catalytic activity of various parameters such as the precursors, solvent, temperature or catalyst/substrate ratio was examined. The process is particularly selective for linear and aromatic aldehydes. The oxidation of adipaldehyde with dioxygen in mild conditions, in the presence of HPA-2 as a catalyst, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The reaction is prolonged with substrates containing electron-donating substituents in the aromatic ring (Table 4, entries, 6-9). These observations clearly show that such active electrondonating groups do not allow smooth oxidation of aldehydes to carboxylic acids because these types of aldehydes can also act as radical scavengers 27 . Previous work 55 showed that irons salts are efficient catalysts precursors for the oxidation of aldehydes.…”
Section: Oxidation Of Other Aldehydesmentioning
confidence: 94%
See 2 more Smart Citations
“…The reaction is prolonged with substrates containing electron-donating substituents in the aromatic ring (Table 4, entries, 6-9). These observations clearly show that such active electrondonating groups do not allow smooth oxidation of aldehydes to carboxylic acids because these types of aldehydes can also act as radical scavengers 27 . Previous work 55 showed that irons salts are efficient catalysts precursors for the oxidation of aldehydes.…”
Section: Oxidation Of Other Aldehydesmentioning
confidence: 94%
“…The oxidation of trans-cinnamaldehyde and citronellal were evaluated under the oxidative conditions of our catalytic system. These substrates contain aldehyde functionality together with an epoxidizable olefinic double bond 27 .…”
Section: Oxidation Of Other Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, H 3+x PV x are also considered as the precursors of in situ-formed pervanadyl cations that would be the true catalysts as suggested by Bregeault et al [50] and El Amrani et al [51], characterized by a higher redox potential than parent H 3+x PV x [29] and therefore may be more effective for oxidation, including aerobic cleavage. Such ejection is accompanied by the formation of an unstable lacunary polyoxometalate (POM) that generates a phosphomolybdate anion.…”
Section: Evolution Of the Catalystmentioning
confidence: 99%
“…Nevertheless, it is worthy to note that the α-positions of ethers can be easily attacked by molecular oxygen (scheme1). Moreover, THF is not friendly for the environmental point of view, and thus must be handled under strict safety conditions 22 .…”
Section: Effect Of Solventmentioning
confidence: 99%